Ex Libris (Nordic Journal of Practical Theology, 2017)
Anne H. Balsnes, Solveig Christensen, Jan Terje Chri-stoffersen, Hallvard O. Mosdøl (red.)Gudstjeneste à la carteØyvind M. Eide: Fridtjov S. BirkeliGiganten og gåten